Variables Reflecting the Mineralization of Bone Tissue From Fracturing Versus Nonfracturing Postmenopausal Nonosteoporotic Women. (20th June 2018) - Rizzo, Sébastien; Farlay, Delphine; Akhter, Mohammed; Boskey, Adele; Recker, Robert; Lappe, Joan; Boivin, Georges
ABSTRACT: Women with equivalent areal bone mineral densities may show a different fracture incidence due to differences in bone intrinsic quality. Previously, Fourier transform infrared spectroscopic imaging (FTIRI) on the same iliac bone biopsies reported here, showed that the only significantly different variable was the carbonate/phosphate ratio, which was decreased in the fracturing group. Nanoindentation showed that fracturing bone was less mechanically heterogeneous than nonfracturing bone and could propagate damage (microcracks) more easily. The hypothesis is that fracturing women have reduced mineralization of bone tissue compared to nonfracturing women. Transiliac bone biopsies were collected from fracturing ( n  = 60, 62.5 ± 7.4 years old) and nonfracturing ( n  = 60, 62.3 ± 7.3 years old) postmenopausal women, to assess the mineralization of bone tissue using digitized microradiography. The degree of mineralization of bone (DMB, g/cm 3 ) and the heterogeneity index (HI, g/cm 3 ) of the DMB were calculated for cancellous (canc), cortical (cort) and total bone. Results were compared to variables from nanoindentation, FTIRI, and histomorphometry. DMB and HI were not significantly different between fracturing and nonfracturing groups. In the nonfracturing group, cort and canc HI were weakly negatively associated with cort and canc DMB ( r ′ = −0.388, p  < 0.003; r ′ = −0.532, p  < 0.0001, respectively). In the fracturing group, DMB and HI were negatively correlated only in canc ( r ′ = −0.295, p  = 0.024). DMB and HI were not associated with nanoindentation variables. Cort and canc DMB were positively associated with mineral‐to‐matrix ratio measured by FTIRI (ratio between mineral and organic matrix representing the relative mineralization of the collagen matrix), and negatively associated with carbonate/phosphate ratio. None of the DMB variables were strongly associated with any of the histomorphometric variables. In conclusion, bone mineralization was not significantly different between fracturing and nonfracturing postmenopausal women, suggesting that bone fragility could be partly due to other variables, such as changes in hydration of bone matrix or an increase of non‐enzymatic crosslinks in bone collagen. © 2018 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.